Assessment of aortic and cerebral haemodynamics and vascular brain injury with 3 and 7 T magnetic resonance imaging in patients with aortic coarctation. Issue 1 (11th January 2023) - Meijs, Timion A; van Tuijl, Rick J; van den Brink, Hilde; Weaver, Nick A; Siero, Jeroen C W; van der Worp, H Bart; Braun, Kees P J; Leiner, Tim; de Jong, Pim A; Zwanenburg, Jaco J M; Doevendans, Pieter A; Voskuil, Michiel; et al.
Abstract: Aims: Coarctation of the aorta (CoA) is characterized by a central arteriopathy resulting in increased arterial stiffness. The condition is associated with an increased risk of stroke. We aimed to assess the aortic and cerebral haemodynamics and the presence of vascular brain injury in patients with previous surgical CoA repair. Methods and results: Twenty-seven patients with CoA (median age 22 years, range 12–72) and 25 age- and sex-matched controls (median age 24 years, range 12–64) underwent 3 T (heart, aorta, and brain) and 7 T (brain) magnetic resonance imaging scans. Haemodynamic parameters were measured using two-dimensional phase-contrast images of the ascending and descending aorta, internal carotid artery (ICA), basilar artery (BA), middle cerebral artery (MCA), and perforating arteries. Vascular brain injury was assessed by rating white matter hyperintensities, cortical microinfarcts, lacunes, and microbleeds. Pulse wave velocities in the aortic arch and descending aorta were increased and ascending aortic distensibility was decreased in patients with CoA vs. controls. Patients with CoA showed a higher mean flow velocity in the right ICA, left ICA, and BA and a reduced distensibility in the right ICA, BA, and left MCA. Haemodynamic parameters in the perforating arteries, total cerebral blood flow, intracranial volumes, and vascular brain injury were similar between the groups. Conclusion: Patients with CoA show an increased flow velocity and reduced distensibility in the aorta and proximal cerebral arteries, which suggests the presence of a generalized arteriopathy that extends into the cerebral arterial tree. No substantial vascular brain injury was observed in this relatively young CoA population, although the study was inadequately powered regarding this endpoint. Graphical Abstract: Graphical Abstract Graphical summary of the main findings in this study. This figure was created using an image from Servier Medical Art (smart.servier.com). PWV, pulse wave velocity; WMH, white matter hyperintensity.